El dilema del mejoramiento integral de barrios : prevención del desplazamiento residencial de barrios legalizados. Estudio de caso Barrio Los Olivos en Bogotá (2021)
Since the 1950s, the government of Bogotá has implemented Comprehensive Neighborhood Upgrade actions (MIB in Spanish) in informal settlements, which begin with their recognition and legalization. Although the objective of these actions is to improve quality of life, paradoxically, legalized neighborhoods in strategic locations are at risk of gentrification and displacement, increasing informality and segregation. This paradox sets up the MIB Dilemma. Studies of the last decade on residential displacement associated with gentrification in Latin America highlight the role of the State in these processes, but few questions the role of MIB. To study this Dilemma, I combine ethnographic techniques with spatial analyzes that allow observe the incidence of MIB actions in the displacement of Los Olivo's residents, a neighborhood legalized in 1996, in Chapinero, Bogotá. The results reveal the weaknesses in i) the political dimension of the MIB...